(untitled) (American Journal of Medical Science and Innovation, 2025)
This study discusses a completely amputated right middle finger in a 9- year-old boy. The study employed a case report relating to a successful distal finger replantation in a 9-year-old child with a double-level injury. A bicycle chain accident caused traumatic amputation at the distal interphalangeal joint level, requiring surgery for replantation. The fingertip’s properties are crucial for tracing, gripping, and protection, hence surgery was attempted. Post-debridement, severely crushed radial and ulnar neurovascular bundles were found. The proximal ulnar digital artery and nerve stumps were affected. The radial neurovascular bundle was crushed with segmental loss evident after exploring post-debridement. Radial distal structures were found to be the least damaged. One proximal digital artery was repaired, and single digital nerve was approximated. The artery was repaired cross-sectionally with the proximal ulnar digital artery anastomosed to the distal radial artery stump. As the damage was complex and a double-level cut, surgery was mainly performed to restore the cosmetic and functional characteristics of the finger and to eliminate the requirement of a donor site using another reconstructive option. This case is important in highlighting the developments and advancements in digital replantation procedures. This is also valid in pediatric cases if complex injuries occur. Besides, all these, essential insights are put into the current literature in the domain of pediatric digital replantation, and this is done by a detailed surgical approach, potential challenges experienced, and the discussion of outcomes.